Can the Trust in Uber-like Platform Use Be Translated into Parcel Logistics? (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Rising expectations for urban logistics are the biggest challenge for parcel service providers. The increased costs posed by obstacles reduce profitability, and providers are forced to develop a novel operating model based on cooperation. The new model can combine what is known so far, which can be integrated into a platform-based system to implement collaborative resource sharing. The implementation of the platform will result in the introduction of a new player and the creation of a partly common ICT background. The platform-based approach is known in the context of the sharing economy initiative, which has also brought a novel trust-based model to life. On the one hand, this article presents a possible business model for parcel logistics providers and, on the other hand, the operation of a third-party IT platform and the method of resource allocation designed to reduce costs. In addition, it presents the possible reasons for the intention to join the platform and the conditions necessary to maintain the platform.